Lipopolysaccharide Associates with Amyloid Plaques, Neurons and Oligodendrocytes in Alzheimer’s Disease Brain: A Review - Zhan, Xinhua; Stamova, Boryana; Sharp, Frank R. (Frontiers in Aging Neuroscience, 2018)
This review proposes that LPS (Lipopolysaccharide, found in the wall of all Gram-negative bacteria) could play a role in causing sporadic Alzheimer’s Disease (AD). This is based in part upon recent studies showing that: Gram-negative E coli bacteria can form extracellular amyloid; bacterial-encoded 16S rRNA is present in all human brains with over 70% being Gram-negative bacteria; ultrastructural analyses have shown microbes in erythrocytes of AD patients; blood LPS levels in AD patients are 3-fold the levels in control; LPS combined with focal cerebral ischemia and hypoxia produced amyloid-like plaques and myelin injury in adult rat cortex. Moreover, Gram-negative bacterial LPS was found in aging control and AD brains, though LPS levels were much higher in AD brains. In addition, LPS co-localized with amyloid plaques, peri-vascular amyloid, neurons, and oligodendrocytes in AD brains. Based upon the postulate LPS caused oligodendrocyte injury, degraded Myelin Basic Protein (dMBP) levels were found to be much higher in AD compared to control brains. Immunofluorescence showed that the dMBP co-localized with β amyloid (Aβ) and LPS in amyloid plaques in AD brain, and dMBP and other myelin molecules were found in the walls of vesicles in periventricular white matter. These data led to the hypothesis that LPS acts on leukocyte and microglial TLR4-CD14/TLR2 receptors to produce NFĸB mediated increases of cytokines which increase Aβ levels, damage oligodendrocytes and produce myelin injury found in AD brain. Since Aβ1-42 is also an agonist for TLR4 receptors, this could produce a vicious cycle that accounts for the relentless progression of AD. Thus, LPS, the TLR4 receptor complex, and Gram-negative bacteria might be treatment or prevention targets for sporadic AD. Keywords: Alzheimer’s disease, Lipopolysaccharide, Cytokines, TLR4, CD14, Myelin, MBP, oligodendrocytes, Amyloid plaque, perivascular amyloid